Competitiveness of Paraguay international agricultural trade: An analysis of the soybean complex - Lesmo-Duarte, Nelson David; Vega-Britez, Gustavo Daniel; Velazquez-Duarte, José Augusto; Lesmo-Duarte, Cristian Reinaldo; Barreto-Perez, Sixto; Paredes-Lopes, Laiana Patricia; Ferreira-Agüero , Marcos Arturo (Revista de Ciencias Agrícolas, 2026)
Agribusiness has become a cornerstone of the Paraguayan economy, with soybeans and their derivatives serving as key contributors to the country’s main source of foreign income. This study investigates Paraguay's competitiveness in its primary commodities, such as soybeans and their derivatives, as well as their market concentration, highlighting its comparative advantage. The study employs the Revealed Comparative Advantage Index (RCA) and the Hirschman-Herfindahl Index (HHI) to assess export competitiveness and concentration. The results indicate that Paraguay maintains a comparative advantage in exporting soybean grain and oil, although soybean meal exhibits a weaker market share. An increase in export concentration toward Argentina was observed, raising concerns about vulnerability to demand fluctuations. However, exports of soybean-derived products are more diversified, which provides stability. The study concludes that to enhance competitiveness, Paraguay must focus on the industrialization of its products and adopt policies that strengthen its export capacity while minimizing dependence on specific markets.